A Review of EFL Formulaic Language Acquisition and Teaching intervention - Chen, Chuanfu; Chen, Songsong (International Journal of Humanities and Education Development (IJHED), 2021)
This paper reviews EFL formulaic language research in international and Chinese domestic academia from the perspectives of language acquisition and language teaching. Current studies have some limitations due to different types of reasons. For example, a lack of representativeness in the selection of target items, a lack of attention to learner’s differences, and a scanty of high-quality EFL formulaic sequences instruction research. Future research can pay more attention to learners’ differences that may affect the acquisition and learning process of the formulaic language, with the aim of exploring effective methods and approaches to improve the competence of EFL learners and promoting the optimization of theories exploring the teaching of EFL formulaic language.